The combination therapy of oncolytic virotherapy - Wang, Yue; Zhu, Mengying; Chi, Huanyu; Liu, Yang; Yu, Guilin (Frontiers in Pharmacology, 2024)
Compared to other cancer immunotherapies, oncolytic viruses possess several advantages, including high killing efficiency, excellent targeting capabilities, minimal adverse reactions, and multiple pathways for tumor destruction. However, the efficacy of oncolytic viruses as a monotherapy often falls short of expectations. Consequently, combining oncolytic viruses with traditional treatments to achieve synergistic effects has emerged as a promising direction for the development of oncolytic virus therapies. This article provides a comprehensive review of the current progress in preclinical and clinical trials exploring the combination therapies involving oncolytic viruses. Specifically, we discuss the combination of oncolytic viruses with immune checkpoint inhibitors, chemotherapy, targeted therapy, and cellular therapy. The aim of this review is to offer valuable insights and references for the further advancement of these combination strategies in clinical applications. Further research is necessary to refine the design of combination therapies and explore novel strategies to maximize the therapeutic benefits offered by oncolytic viruses.